Amine-functionalised poly(glycidyl methacrylate) hydrogels for Congo red adsorption - Gokkus, Kutalmis; Sengel, Sultan Butun; Yildirim, Yeliz; Hasanbeyoglu, Soner; Butun, Vural (Emerald, 2023)
Dyes are one of the most common pollutants in wastewater due to their widespread use. Therefore, to protect aquatic ecosystems, dyes must be treated in situ and/or in vivo. In this study, poly(glycidyl methacrylate) (PGMA) gels were synthesized. PGMA gels were subsequently modified with diethylenetriamine (DETA) and tetraethylenepentamine (TEPA) containing different numbers and lengths of amino groups to obtain PGMA–NH2 hydrogels. Finally, these hydrogels were used for the adsorption of Congo red (CR). Adsorption studies were carried out according to the batch adsorption procedure. From the study, the contact time was found to be 40 min and the highest adsorption capacities of 196 and 147 mg/g for PGMA–DETA and PGMA–TEPA were reached, respectively. Isotherm and kinetic experiments showed that the adsorption obeys the Freundlich isotherm and pseudo-second-order equation. The CR dye is an anionic indicator dye. These results showed that PGMA–NH2 hydrogels have significant potential for efficient adsorption of anionic dyes.
Keywords: Heavy-Metal Ions; Activated Carbon; Dye; Nickel; Adsorbent; Composite; Waste-Water; Removal; Aqueous-Solutions; Methylene-Blue; 6. Clean water